2020
DOI: 10.1155/2020/1459368
|View full text |Cite|
|
Sign up to set email alerts
|

circFAT1(e2) Promotes Papillary Thyroid Cancer Proliferation, Migration, and Invasion via the miRNA-873/ZEB1 Axis

Abstract: Circular RNAs (circRNAs) play an extremely important regulatory role in the occurrence and development of various malignant tumors including papillary thyroid cancer (PTC). circFAT1(e2) is a new type of circRNA derived from exon 2 of the FAT1 gene, which is distributed in the cytoplasm and nucleus of PTC cells. However, so far, the role of circFAT1(e2) in PTC is still unclear. In this study, circFAT1(e2) was found to be highly expressed in PTC cell lines and tissues. circFAT1(e2) knockdown suppressed PTC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…This effect is also commonly observed in TC: CircFAT1 (e2) has a function similar to that of CIRS-7 and has a binding site for miR-873. CircFAT1 is highly expressed in PTC tissues and cells and serves as an miRNA sponge to vastly downregulate miR-873 expression, thus upregulating the activity of zinc finger E-box binding homeobox 1 and ultimately promoting the growth, migration and invasion of PTC cells ( 34 ).…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“…This effect is also commonly observed in TC: CircFAT1 (e2) has a function similar to that of CIRS-7 and has a binding site for miR-873. CircFAT1 is highly expressed in PTC tissues and cells and serves as an miRNA sponge to vastly downregulate miR-873 expression, thus upregulating the activity of zinc finger E-box binding homeobox 1 and ultimately promoting the growth, migration and invasion of PTC cells ( 34 ).…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“…Previous studies have shown that circFAT1(e2) is a new circRNA derived from exon 2 of the FAT1 gene [ 16 ]. In PTC, circFAT1(e2) plays a carcinogenic effect by promoting cell invasion and metastasis and is a potential new target for PTC therapy [ 17 ]. It is found in gastric cancer (GC) that the overexpression of circFAT1(e2) inhibits the proliferation, migration, and invasion of GC cells and is related to the overall survival rate of GC patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if tissue circFAT1 expression levels in a biopsy sample or resected specimen are low, additional treatments need to be considered, even for patients with early-stage cancer. Evidence is accumulating to show that circFAT1 exerts both tumor-promoting 17,[20][21][22] and tumor-suppressive effects. 18,19 Tumor-suppressive effects have been reported for adenocarcinomas of the gastrointestinal tract, 18,19 but not for squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression and oncological significance were initially reported for osteosarcoma in 2018 17 and subsequent studies reported similar findings for other cancer types. CircFAT1 functions as a tumor promoter or suppressor in specific cancers by sponging miRNAs and repressing their downstream pathways; [18][19][20][21][22] however, it has not yet been reported as a prognostic biomarker in any cancers. The present study investigated the biological function of circFAT1 and its potential as a prognostic biomarker in ESCC.…”
mentioning
confidence: 99%